Unsettled urbanization: spatiality of urban growth in Dodoma, Tanzania - Neema Simon Sumari; Patrick Brandful Cobbinah; Nathan Tetteh; Michael Odei Erdiaw-Kwasie (Geo-spatial Information Science)
Rapid urbanization has traditionally stifled socio-economic development and led to limitless urban expansion across African cities. However, limited research has focused on land use simulation and modeling as useful analytical tools to analyze, understand, and respond to urban transformation due to rapid changes. With the ongoing threat of climate change and rapid urbanization across African cities, this paper uses Dodoma, Tanzania, as a case study to (i) explore the spatial distribution of land use and urban extent between 2000 and 2022; (ii) establish the driving variables that frame and dictate patterns of land use changes; and (iii) develop a future simulation of urban land use of the city for 2050 to support sustainable urban development. We utilize the TerrSet and Land Change Modeler (LCM) models to analyze the Land Use/Land Cover (LULC) patterns from 2000 to 2022. The results indicate that the spatial extent of Dodoma urban increased by 154.61 km2 between 2000 and 2022 double the rate of inhabitant growth (5.8% per annum) during the same period. The accuracy of the actual land use was confirmed with a confusion matrix and Kappa statistics of 94.71% and 0.4916, respectively. We argue that knowledge of the current state and simulated outcomes of future urban expansion is critical to Dodoma’s future land use planning and management. Our findings provide guidelines and highlight possible options for sustainable urban land use practices in similar urbanizing African cities. We conclude by advancing a research agenda on African urbanization planning and management, drawing upon a land use modeling approach grounded in responsibility.